Peregrinos da fé na Amazônia urbana: faces do individualismo religioso - PINTO, Daniel Silva (Universidade Federal do Pará, 2024)
The study of the dynamics of religiosity in modern times, especially on the processes of individual identity construction, indicate more systematic and far-reaching investigations on the effects of modern religious individualism in the configuration of national religious fields; this phenomenon affects the size and measurement of traditional religions such as Christianity and, mainly, how institutionalized religion is affected in its ability to transmit its memory or authorized religious heritage. The analysis of such a phenomenon in Brazil, at its theoretical level, in this work - which could lead to the production of a sociological literature of religion with less focus on institutions and more on the individual in his free transit through the immense national symbolic-religious market - is centered on Danielle Hervieu-Léger's concept of the pilgrim. The figure of the pilgrim would be the symbol of a new religiosity - or could we call it spirituality? - at the beginning of this century, always on the move and with no vocation for traditional religiosity, accustomed to symbolic borders and fixed rituals. In the Amazon, this more fluid and deterritorialized religiosity can be better exemplified and identified in its urban dimension and with more intensity in the groups practicing those generically classified as New Age religions in fusion or hybridity with practices and cosmologies of the Amazonian religious imaginary. Its adherents or practitioners emphasize more a religiosity of personal search or spiritual development in contrast with the traditional religiosities of Christian transcendence. In turn, Christians, Catholics and Evangelicals, do not cease to manifest practices and beliefs hybridized with other symbolic-religious matrices, and even an intense transit, whether internal or endogenous, that is, between the diversity of evangelical denominations, (Pentecostal and Neo-Pentecostal ), or external, exemplified by the double or multiple belongings of Catholics.